Investigation of antibacterial and antioxidant properties of three medicinal plants from Gaziantep, Turkey - Sinem Aydin; Mustafa Sümbül (European Journal of Biological Research, 2022)
Current research aimed to reveal antibacterial and antioxidant properties of acetone and ethyl acetate extracts of Phlomis armeniaca, Echinophora tenuifolia subsp. sibthorpiana and Moringa oleifera plants obtained from herbalists in Gaziantep. Extracts of P. armeniaca, E. tenuifolia subsp. sibthorpiana and M. oleifera plants have antibacterial effect at varying degrees against test bacteria. Both ethyl acetate and acetone extracts of P. armeniaca plant exhibited higher antibacterial activity than studied other plant extracts. It was also found that the antioxidant activity increased with increasing concentrations. Since antioxidant and antibacterial activities were observed in almost all of the tested plant extracts, it was concluded that P. armeniaca, E. tenuifolia subsp. sibthorpiana and M. oleifera plants could be natural sources of antioxidant and antibacterial.